Integration of a case-based reasoning and an ontological know ledge base in the system of intelligent support of finite element analysis - Wriggers, Peter; Siplivaya, Marina; Zhukova, Irina; Kapysh, Alexander; Kultsov, Anton (Computer Assisted Methods in Engineering and Science; Vol 14 No 4 (2007), 2022)
The process of engineering analysis, especially its preprocessing stage, comprises some knowledge-based tasks which influence the quality of the results greatly, require considerable level of expertise from an engineer; the support for these tasks by the contemporary CAE systems is limited. Analysis of the knowledge and reasoning involved in solving these tasks shows that the appropriate support for them by an automated system can be implemented using case-based reasoning (CBR) technology and ontological knowledge representation model. In this paper the knowledge-based system for intelligent support of the preprocessing stage of engineering analysis in the contact mechanics domain is presented which employs the CBR mechanism. The knowledge representation model is formally represented by the OWL DL ontology. Case representation model, case retrieval and adaptation algorithms for this model and the automated system are described.